2017
DOI: 10.1520/jte20160221
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Durability Properties of High-Volume Fly Ash Mortar Composites

Abstract: The use of fly ash, a common industrial byproduct waste, is gaining popularity, especially in developing countries, in addressing environmental concerns surrounding the construction industry, such as reducing waste and CO2 emissions. However, the full potential of fly ash usage is yet to be exploited. The physical, mechanical, and durability properties of fly ash in concrete are well documented; in contrast, its durability properties in mortar require further investigations. The present study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…According to their results, it was observed that the highest ultrasonic wavelength was in the concrete with 40% fly ash replacement. Aydın and Balkis [ 81 ] noted in their study that the use of fly ash in concrete contributed to the formation of the C-S-H structure, which contributes to the strong and durable structure of the concrete. The C-S-H structure formed by fly ash causes it to fill the gaps and form an impermeable material.…”
Section: Resultsmentioning
confidence: 99%
“…According to their results, it was observed that the highest ultrasonic wavelength was in the concrete with 40% fly ash replacement. Aydın and Balkis [ 81 ] noted in their study that the use of fly ash in concrete contributed to the formation of the C-S-H structure, which contributes to the strong and durable structure of the concrete. The C-S-H structure formed by fly ash causes it to fill the gaps and form an impermeable material.…”
Section: Resultsmentioning
confidence: 99%
“…This article investigates three workability range (0 mm, 100 mm and 200 mm) and seven mixture groups. The groups are all optimized in a previous researches [2] , [3] , [4] , [5] . The data presented here examined the mixture ingredients of fly ash, cement, silica fume, lime and water reducers.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The detailed of the dataset presented here can be found in [1] . Additionally, the existing models proposed in previous studies for mortars and cement paste [2] , [3] , [4] , [5] , [6] , [7] were used to check the applicability in controlled low strength applications. The regression analysis of test data for 1512 samples were used to predict the effects of mixture ingredients in those applications to exhibit novel mixture design methods ( Fig.…”
Section: Datamentioning
confidence: 99%
“…Bu kapsamda yapılan çalışmada uçucu kül kullanımının yanı sıra inceliğinin de beton yapısının boşluk özelliği üzerinde olumlu etki yarattığı yapılan deney sonuçları ile belirlenmiş ve literatürle sonuçlar karşılaştırılmıştır. Aydın ve Balkis [72] çalışmalarında çimento yerine % 20, % 40, % 60 ve % 100 oranlarında uçucu kül kullanımı ile üretilen 50, 150 ve 250 mm çökme değerlerine sahip betonların ultrasonik darbe hızı değerlerini belirlemişler. Elde ettikleri sonuçlara göre çimento yerine uçucu kül eklemenin yapının sağlamlığını ve dayanımını arttırıcı C-S-H yapısının oluşmasına katkı sağladığını belirtmişler.…”
Section: Bulgular Ve Tartışmaunclassified